Factors Influencing Injury Severity Scores Among War Casualties along the Thai–Myanmar Border: Experience from Maesot Hospital (2020–2024) - Konjara, Singha (Journal of the Association of General Surgeons of Thailand under the Royal of Patronage of HM the King, 2025)
Background: In the context of ongoing armed conflicts and political instability in Southeast Asia, particularly along the Thai–Myanmar border, war-related injuries pose a significant public health challenge. These injuries are complex and have a profound impact on emergency medical care. Assessing the severity of war-related trauma is crucial for prioritizing treatment and guiding decision-making in trauma and emergency surgery. Therefore, this study aims to identify factors influencing injury severity scores (ISS) in war casualties admitted to Maesot Hospital, a major referral center along the Thai–Myanmar border. Methods: A retrospective study was conducted using medical records of war-injured patients treated at Maesot Hospital between 2020 and 2024. A total of 212 patients were included and categorized into two groups based on their ISS scores: ISS <16 (n=53) and ISS ≥16 (n=169). Descriptive statistics and multiple logistic regression analysis were performed to identify factors associated with higher ISS. Results: There was no significant association between sex and ISS severity (p=0.79). However, age was a significant factor, with patients aged 35–44 years being more likely to sustain severe injuries (p=0.04). Additionally, inpatient status was strongly associated with higher ISS (p<0.01), indicating that patients requiring hospitalization had more severe injuries. Regarding injury location, multiple trauma involving multiple body regions was the strongest predictor of higher ISS (Adjusted OR = 9.69, 95% CI: 1.05–88.65, p=0.04). Conversely, head and neck injuries, abdominal and pelvic injuries, and upper limb injuries did not show significant associations with ISS severity. Conclusions: and Recommendations: Key determinants of severe injury in war casualties include patient age, inpatient status, and multiple trauma affecting multiple body regions. These findings highlight the importance of these variables in predicting trauma severity and clinical outcomes. The study underscores the need for strategic resource allocation, optimized trauma triage, and improved surgical management protocols in conflict-affected border regions. Implementing ISS-based triage in battlefield trauma care settings could enhance patient survival and improve healthcare efficiency in resource-limited environments.